Fine particulate matter and incidence of metabolic syndrome in non-CVD patients: A nationwide population-based cohort study - Lee, Seulbi; Park, Hyesook; Kim, Soontae; Lee, Eun Kyung; Lee, Jiyoung; Hong, Young Sun; Ha, Eunhee (International Journal of Hygiene and Environmental Health, 2019)
Background: It has been reported that particulate matter (PM) is associated with cardiovascular diseases (CVD) while metabolic syndrome is also an important risk factor for CVD. However, few studies have investigated the epidemiological association between PM and metabolic syndrome. Objective: To investigate the association between one-year exposure to PM with an aerodynamic diameter <2.5 μm (PM 2.5 ) and the risk of metabolic syndrome in Korean adults without CVD. Methods: Exposure to PM 2.5 was assessed using a Community Multiscale Air Quality (CMAQ) model. Metabolic syndrome was defined by National Cholesterol Education Program Adult Treatment Panel III. Andersen and Gill model with time-varying covariates, considering recurrent events, was used to investigate the association between one-year average PM 2.5 and the risk of incident metabolic syndrome in 119,998 adults from the national health screening cohort provided by Korea National Health Insurance from 2009 to 2013. Results: Higher risk of metabolic syndrome, waist-based obesity, hypertension, hypertriglyceridemia, low HDL cholesterol, and hyperglycemia were significantly associated with a 10-μg/m 3 increase in PM 2.5 [adjusted hazard ratio (HR): 1.070, 1.510, 1.499, 1.468, 1.627 and 1.380, respectively]. In addition, the risk of metabolic syndrome associated with PM 2.5 exposure was significant in the consistently obese group (obese at baseline and endpoint). Conclusion: Exposure to one-year average PM 2.5 is associated with an increased risk of metabolic syndrome and its components in adults without CVD. These associations are particularly prominent in the consistently obese group (obese at baseline and endpoint). Our findings indicate that PM 2.5 affects the onset of MS and its components which may lead to increase the risk of CVD.
Keywords: Air Pollutants; Cohort Studies; Dyslipidemias; Environmental Monitoring; Female; Humans; Hyperglycemia; Hypertension; Incidence; Male; Metabolic Syndrome; Middle Aged; Obesity; Particulate Matter; Republic of Korea; Risk Factors; Air pollution; Andersen-Gill model; Body mass index; Fine particulate matter; Metabolic syndrome; Recurrent events